Association between prior use of anti-diabetic medication and breast cancer stage at diagnosis. Issue 2 (1st February 2021) - Fahim, Shahariar Mohammed; Hsu, Chiu-Hsieh; Lin, Fang-Ju; Qian, Jingjing; Chou, Chiahung
ABSTRACT: Background: Knowledge regarding antidiabetic medication (ADM) use prior to breast cancer (BC) diagnosis remains limited. The objectives were to (1) evaluate if the prior use of ADM was associated with BC stage at diagnosis and (2) identify and compare patient characteristics among BC patients using different ADMs. Research design and methods: Newly diagnosed female BC patients exposed to any medication during one year prior to cancer diagnosis were identified in 2008–2013 Linked Surveillance, Epidemiology, and End Results (SEER)-Medicare database. Stage at diagnosis, categorized as early and advanced, was the primary outcome. Chi-square tests were used to compare characteristics and logistic regression models were applied to examine the effect while controlling for patient's characteristics. Results: A total of 1, 719 female BC patients used ADM while 6, 084 patients were non-ADM users. Although a higher proportion of ADM users (20.36%) were diagnosed with advanced stage compared to the non-ADM users (14.46%), the difference was not statistically significant after adjusting for the patients' characteristics. Besides, insulin users were more likely to be diagnosed with advanced stage (adjusted odds ratio 1.69; 95% CI 1.15, 2.48) compared to metformin users. Conclusions: The association between ADM use and BC diagnostic characteristics varied based on different treatments.